Removal of 2-nitrophenol by catalytic wet peroxide oxidation using carbon materials with different morphological and chemical properties - Rui S. Ribeiro (2013)
Carbon materials with distinct morphological and chemical characteristics, namely activated carbons, carbon nanotubes, glycerol-based carbon materials and carbon xerogels, were tested for the removal of 2-nitrophenol (2-NP) in aqueous solutions, either by pure adsorption or by catalytic wet peroxide oxidation (CWPO). The results obtained in adsorption experiments carried out at pH 3, T=323 K, adsorbent load of 0.1 g L-1 and 2-NP concentration of 100 mg L-1, show that, in general, the activated carbons have superior adsorption performances compared to the other carbon materials tested, exhibiting removals of 2-NP up to 316 mg g(-1) after 150 min of adsorption. In the CWPO experiments, whilst the activated carbons and carbon xerogels were not able to improve the removal of 2-nitrophenol, in comparison with the removals observed in pure adsorption experiments performed at the same conditions, the use of carbon nanotubes (CNT) and a glycerol-based carbon material (GBCM) resulted in increments in the removal of 2-NP as high as 83% and 56%, respectively. Removals of about 80% after only 30 min and higher than 90% after 150 min of reaction (equivalent to 929 mg g(-1)) are reached when using CNT as catalysts. The leaching of Fe (present as impurity in the CNT) at the end of the CWPO experiment was found to be negligible. The opposite was observed for classical iron supported on activated carbons, with catalytic activities resulting from the homogeneous contribution of Fe that is leached to the liquid phase. The superior performances found for CNT, makes this catalyst a promising system for CWPO.